Evaluación de la piedra termal como cimentación en la interacción suelo-estructura en edificaciones medianas - Paucar Chanca, Fortunato (2023)
The present study aims to determine the influence of thermal stone as a foundation in the soil-structure interaction, for this purpose, samples of thermal stone were extracted in situ and subsequently tested in the laboratories of the Professional School of Civil Engineering of the National University of Huancavelica to determine the modulus of elasticity, density, saturated humidity, friction angles and cohesion, also in the same way the properties of a conventional medium height building, which were processed to determine the load capacity of thermal stone using the Xiao-Li Yang and Jian-Hua Yin methods for rigid soils, the dynamic models proposed by Villarreal (2006), to determine the stiffness coefficients in both saturated and dry states, and finally, with the data of the latter, a dynamic analysis of a five-story dual type building oriented to lodging was performed, considering soil-structure interaction with the help of the SAP 2000 program, obtaining the following results: the load capacity of the thermal stone in dry state is 4.42 kg/cm2 and saturated state 4.19 kg/cm2, concluding that it does not significantly influence the results, with respect to the stiffness coefficients of the saturated state they are greater in minimum proportions, with greater difference in the Sargsian method and smaller in Barkan, concluding that it does not significantly influence the results.